Optimal Solution of Transportation Problem Using Linear Programming: A Case of a Malaysian Trading Company - Ghazali, Zulkipli (2012)
Managers regularly make decisions pertaining to the effective and efficient allocation of resources to various activities in meeting organizational objective. The task of deciding the optimum plan for distributing goods at the lowest cost possible is a case in point. Minimizing cost of transportation is fundamental for companies in the midst of highly competitive business environment. This paper highlights the application of linear programming and spreadsheet that facilitate managers in a Malaysian Trading Company in determining the optimum transportation plan that leads to the lowest transportation cost of polymer from four plants to four demand destinations. It also discusses sensitivity technique in analyzing the impact of uncertainty of unit shipping cost to the total shipping cost of the trading company.